AN EDUCATIONAL INTERVENTION PROGRAMME ON HAZARDS OF PLASTIC WASTE AND ITS DISPOSAL AMONG ADULTS: A RURAL COMMUNITY BASED STUDY - Manuel, Jincy; Varghese, Jincy; Jose, Jini; Thomas, Jintu K; Joseph, Jinu; Shettigar, Divya (Journal of Health and Allied Sciences NU, 2015)
Introduction: Plastic is everywhere in today's lifestyle. It is used for packaging, protecting, serving, and even disposing of all kinds of consumer goods. Improper plastic disposal has become a leading problem in both developed and developing countries. As plastic is non-biodegradable in nature, it remains in environment for several years and disposing plastic wastes at landfill are unsafe and has led to various health problems. So researcher felt it is vital that adults should possess knowledge on hazards of plastic wastes and its disposal.Method: In this study cross sectional descriptive survey was used. Adults were selected through probability simple random sampling. The data was collected using a pretested structured questionnaire. The structured-teaching programme was administered at the end of the pre-test. The post-test was carried out after 7 days, using the same tool as the pre-test. The data was analysed using SPSS version 16 and the results expressed as proportions.Results: A total of 100 adults were included in the study. Analysis of data revealed pre-test knowledge score was 42.52%.Considering the level of knowledge of adults, a structured teaching programme was administered. The post-test knowledge score was 80.48%. Hence comparison in pre-test knowledge score and post-test percentage of hazards of plastic waste and its disposal was approximately 37.96%. A significant association between source of information and post-test knowledge was found.Conclusion: A significant number of adults had inadequate knowledge. So researcher felt that awareness programmes regarding hazards of plastic waste and its disposal should be emphasized.
Keywords: Plastic wastes; Structured teaching programme; Effectiveness; Knowledge; Rural community adults